First measurement of π-e→π-eγ pion virtual compton scattering - Ocherashvili, A. (2002)
Pion virtual compton scattering (VCS) via the reaction π-e→π-eγ was observed in the Fermilab E781 SELEX experiment. SELEX used a 600 GeV/c π- beam incident on target atomic electrons, detecting the incident π- and the final state π-, electron and γ. Theoretical predictions based on chiral perturbation theory are incorporated into a Monte Carlo simulation of the experiment and are compared to the data. The number of reconstructed events (=9) and their distribution with respect to the kinematic variables (for the kinematic region studied) are in reasonable accord with the predictions. The corresponding π- VCS experimental cross section is σ=38.8±13 nb, in agreement with the theoretical expectation of σ=34.7 nb.